THE REASON FOR LOW ACCESS OF HIGH-QUALITY EDUCATION AND MEDICAL SERVICES (Globalization and Business, 2023)
In the article - “The reason for low access of high-quality education and medical services” - the reasons for the rise of the education crisis in the world in the 70s, low results in the education system in Georgia, reduction of the number of pupils compared to previous years, etc. are discussed.  In 1999-2000, 714 400 pupils were studying in secondary schools of Georgia and in 2017-2018 only 575 100. Education does not have access not only for the Georgian population, but moreover, for the Subsahari, the Asian and Latin American population. There are four classes (and lower ones) educated people there and the share of educated population is very high.  The same situation is in healthcare. Inequality in Medical Healthcare has wide scales in poor countries. Children’s and women's mortality there are higher than in rich countries. Georgia is a poor country and the situation is the same in real, but the statistics office of Georgia does not publish this information in public as regarding the poor and rich people. But the fact that in 2000 the mortality rate for every 1,000 people in Georgia was 9, 8 units in 2000, and in 2017 - 12, 8 units, means that access to quality medical services has not been reduced but increased.  The article ends with a summary conclusion in which the author encourages the authorities to take care of the reduction of inequalities in the population.